Importance of healthy lifestyle factors and ideal cardiovascular health metrics for risk of heart failure in Chinese adults. (21st December 2021) - Yang, Ruotong; Lv, Jun; Yu, Canqing; Guo, Yu; Bian, Zheng; Han, Yuting; Yang, Ling; Chen, Yiping; Du, Huaidong; Liu, Jianjun; Qu, Chan; Chen, Junshi; et al.
Abstract: Background: The relative importance of healthy lifestyle factors and cardiovascular health metrics for the risk of heart failure is uncertain in Chinese populations. We aimed to compare the strength of associations between healthy lifestyle factors and ideal cardiovascular health metrics in the risk of heart failure in middle-aged Chinese adults. Methods: A healthy lifestyle score (HLS) was constructed using smoking, drinking, physical activity, diet, body mass index and waist circumference, and compared with a more comprehensive set of metrics that included cardiovascular-disease risk biomarkers (blood pressure, blood glucose and blood lipids) in addition to the HLS. This broader set of factors [called 'ideal cardiovascular health metrics' (ICVHMs)] was evaluated in 487 197 participants in the China Kadoorie Biobank. Results: A total of 4208 incident cases of heart failure were recorded during a median follow-up of 10 years. Both HLS [hazard ratio (HR), 0.88; 95% confidence interval (CI), 0.85, 0.91] and ICVHMs (0.87: 0.84, 0.89) were inversely associated with risk of heart failure ( P < 0.001 for linear trend). Compared with participants with 0–1 HLS, the multivariable-adjusted HR of those with 4–5 HLS was 0.68 (0.59, 0.77). Compared with participants with 0–2 ICVHMs, the adjusted HR (95% CIs) of those who had 7–8 ICVHMs was 0.47 (0.36, 0.60). ICVHMs were more strongly predictive of risk of heart failure (area under curve, 0.61 vs 0.58, P < 0.001) than healthy lifestyle factors alone. Conclusions: Higher levels of healthy lifestyle factors and ICVHMs were each inversely associated with heart failure, and lifestyle factors combined with cardiometabolic factors improved the prediction of heart failure compared with healthy lifestyle factors alone.